Perspectivas do potencial bioeconômico de plantas ornamentais no município de Benjamin Constant, AM - Almeida, Karen Priscila Cartimare (Brasil, 2025)
Ornamental plants play a crucial role in the aesthetics and environmental balance of urban and rural areas. However, it is interesting to note that, although the inland region of Amazonas is abundant in biodiversity and has potential for the cultivation of these plants, their commercialization is often limited. This can be attributed to a number of factors, including lack of commercial infrastructure, limited access to external markets, and the predominance of an economy focused on other activities. The aim of this research was to investigate the bioeconomic potential of ornamental plants in Benjamin Constant-AM. The development of the work was carried out in the municipality of Benjamin Constant, in the state of Amazonas/Brazil, on the triple border with Colombia and Peru, more precisely in 5 neighborhoods of the municipality, namely Cohabam, Umarizal, Eduardo Braga, Bom Jardim and Centro. The data collection instrument was interviews with residents who grow ornamental plants using the “snowball method”. The data and species were tabulated in an Excel spreadsheet, which generated tables and graphs. In total, 116 species of ornamental plants were identified in the backyards of the interviewees, most of which were plants with lush, showy foliage and not with large, exuberant flowers. In conclusion, the study of the species and botanical families of ornamental plants revealed a predominance of exotic species, originating from various parts of the world, mainly from Central America, Africa and Asia, while plants native to the Amazon region were found in small numbers. If a municipality in the interior of Amazonas begins to invest in increasing the economic potential of the commercialization of ornamental plants, it opens up significant new opportunities for local development. With the scarcity of this market in the region, there is a great deal of room for exploration, especially because Amazonas is rich in biodiversity and can produce exclusive varieties of plants that attract both the local market and tourists and consumers from other states.